Pemberdayaan Posyandu Lansia Melalui Pelatihan Pembuatan Kwetiau Labu Kuning Sebagai Alternatif Makanan Tambahan Bergizi - Titisari Juwitaningtyas; Lisna Zahrotun; Dewi Soyusiawaty; Eni Purwaningsih (Indonesian Journal Publisher, 2023)
Lansia (elderly) is a group of people aged 60 years and over. In an effort to maintain the quality of life of the elderly, the government of the Republic of Indonesia formed an organization called Posyandu Lansia. Posyandu Lansia is a forum for the elderly that is useful for health services, both promotive and preventive efforts. One of the elderly posyandu in Bantul Regency, Yogyakarta Special Region which is active in its activities is Posyandu Lansia Wredho Utomo. There are 7 posyandu members. In the community service activities carried out, the program regarding healthy food is chosen as the main program. The healthy food program chosen was a training program for making independent food using processed kwetiau modified with pumpkin or pumpkin. Kwetiau is a food diversification based on processing from rice flour and tapioca flour. To increase the nutritional content, a pumpkin is added. Limited access due to the COVID-19 pandemic has resulted in this training being delivered in the form of a video which is then practiced independently by participants in their respective homes. According to the assessment of the participants, all participants stated that the videos they made were considered interesting and effective and most of them said the videos that were delivered made the participants enthusiastic.